(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Manual AMB, Gabato NAS, Jetuya QB, Alimbon JA. 2022. Floristic composition, structure, and diversity of mangroves in the coastal areas of Mabini, Davao de Oro, Philippines. Biodiversitas 23: 4887-4893. Biodiversity and stand structure assessments of mangrove communities are important for their management and conservation. However, this aspect of mangrove ecology in the Davao Gulf is not yet fully explored, particularly in the coastal areas of Mabini, Davao de Oro, Philippines, despite being proclaimed as a protected area. Hence, this study assessed the species composition, structure and diversity of mangroves in the coastal areas of Mabini, Davao de Oro, Philippines. Using the belt transect method, 35 plots with 10 m x 10 m each were established and surveyed. Results revealed that the area is home to eight species belonging to six genera and five families. One vulnerable species, Avicennia rumphiana, was recorded on the study site. Of the identified species, Rhizophora apiculata was the most important species, with an importance value index of 144.41 %. Meanwhile, the surveyed mangrove communities had a mean diameter at breast height of 10.96 cm, a basal area of 27.93 m² ha?¹, and a mean density of 4192 stems ha?¹. Diversity analysis indicated that the sampled sites had low species biodiversity (H’ = 1.098), low species richness (R = 0.9601), and less even species distribution (J = 0.5280). These results add to the existing knowledge about mangrove communities in Davao Gulf. More importantly, they serve as important baseline information relevant to the management, protection, and conservation of mangroves within the Mabini Protected Landscape and Seascape.